Tenth International Symposium on the Application of Computer Methods in the Mineral Industry (The Southern African Institute of Mining and Metallurgy)
DECEMBER, 1971 The Wanders Club, Johannesburg Sunday, 9th April, to Friday, 14th April, 1972 The Tenth Symposium which is the first ever held outside the North American continent is being organised by the South African Institute of Mining and Metallurgy (with the South African Council for Scientific and Industrial Research and the South African Council for Automation and Computation), in collaboration with the previous co-sponsors. '" The programme includes over 60 papers from thirteen different countries. Attendance promises to be good and interested parties who have not yet registered are earnestly requested to do so without delay. The closure date for registration application is 31st January, 1972. The objective of this symposium is to pool experience and knowledge and to discuss new and potential developments for the planning and control of mineral projects. The papers which are to be presented will indicate the progress which has been made in this direction through the successful application of operations research, mathematical, statistical and computer methods. The intention is to bring together those persons responsible for managing various operations in the mineral industry with those engaged in the development of such mathematical and computer techniques as could assist this management. All interested parties are welcome. PRE-REGISTRATION (please return enclosed form as soon as possible). Applications for registration close on January 31, 1972. The fee payable on application will be R70. Late applications may, subject to vacancies being available,